Initial goals, goal trajectories, and changes in perceived resolvability during serial arguments. Issue 1 (16th November 2020) - Worley, Timothy; Liu, Esther; Vanderbilt, Rachel
Abstract: This study examined how dyadic patterns of goal importance during a serial argument interaction predict changes in perceptions of argument resolvability over the course of a specific episode. Seventy romantic couples engaged in a 7‐min discussion of a current serial argument and used a video‐assisted recall method to report their goals at each minute. Although arguers' initial goals did not predict changes in perceptions of resolvability, increases in a partner's endorsement of partner‐identity goals predicted increases in individuals' own perceptions of resolvability. Conversely, increases in a partner's endorsement of self‐identity goals predicted declines in individuals' perceived resolvability. Results suggest that trajectories of identity‐focused goals during serial argument episodes may shape the progress of argument perceptions toward or away from resolvability.